Directions of attack and their effectiveness of male judo medalists at the Olympic competitions - Amar AIT ALI YAHIA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: To perform a technical action, the elite judo athlete examines the direction of attack relative to the opponent's body position. This study aimed to analyze and compare the most frequent and effective attack directions carried out by male Olympic medalists. Materials and Methods: A sample of 112 male medalists performed 3,664 attacks in four Olympic tournaments (2004-2016). ANOVA (one factor) determined inter and intra-Olympic comparisons, followed by the post hoc Bonferroni test (p< 0.05). Eta squared η2 and Cohen's d calculated the effect size, respectively. Results: Olympic medalists oriented their attacks principally in right forward (30.5±11.3%), left forward (29.9±10.5%), left backward (18.8±8.1%), and right backward (15.8±6.1%). The effectiveness of right forward (25.7±13.1%) and left forward (26.2±12.5%) dominates left backward (20.5±10.1%) and right backward (15.5±9.7%), respectively. In terms of frequencies and effectiveness, the contribution of secondary directions is negligible. Conclusions: Attacking in eight orientations made the defense vulnerable. Beside the uncertainty and unpredictability, they created more points of imbalance to overcome defensive issues.